Hints of Better Survival With Surgery Than Radiation Therapy in Stage I NSCLC - Mayfield, Eleanor (MD Conference Express, 2015)
Results from a propensity-matched cohort study suggest that long-term outcomes for patients with stage I non–small cell lung cancer may be superior with surgery than with stereotactic body radiation therapy.